STRATEGI PENGEMBANGAN DIVERSIFIKASI PANGAN LOKAL DI KALIMANTAN BARAT - Imelda, Imelda; Kusrini, Novira; Hidayat, Rakhmad (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
The purpose of this study is to develop strategies that can be applied in the development of local food diversification in West Kalimantan. The data used are primary data and secondary data. Variables examined included internal factors (strengths and weaknesses) and external factors (opportunities and threats) in the development of local food diversification in West Kalimantan. Descriptive data were analyzed qualitatively to describe the pattern of food consumption in West Kalimantan and continued with a SWOT analysis to develop strategies for the development of local food diversification in West Kalimantan. The analysis showed that the strategy for the development of local food diversification in West Kalimantan is SO strategy (Strengths - Opportunities), namely: 1) increase the synergy between the government and the micro, small and medium enterprises for the development of food products locally, 2) the use of communications and systems market information in improving the marketing of local food products on micro, small and medium enterprises, and 3) utilization of unutilized agricultural land to improve the quality and quantity of local food products.Tujuan penelitian ini adalah untuk menyusun strategi yang bisa diterapkan dalam upaya pengembangan diversifikasi pangan lokal di Kalimantan Barat. Data yang digunakan adalah data primer dan data sekunder. Variabel yang diteliti meliputi faktor internal (kekuatan dan kelemahan) serta faktor eksternal (peluang dan ancaman) dalam pengembangan diversifikasi pangan lokal di Kalimantan Barat. Analisis data dilakukan secara deskriptif kualitatif untuk menggambarkan pola konsumsi pangan masyarakat Kalimantan Barat dan dilanjutkan dengan analisis SWOT untuk melakukan penyusunan strategi pengembangan diversifikasi pangan lokal di Kalimantan Barat. Hasil analisis menunjukkan bahwa strategi yang bisa diterapkan untuk pengembangan diversifikasi pangan lokal di Kalimantan Barat yaitu strategi SO (Strengths Opportunities), yaitu peningkatan sinergi antara pemerintah dengan pelaku sektor UMKM (Usaha Mikro, Kecil dan Menengah) untuk pengembangan produk pangan lokal, pemanfaatan komunikasi dan sistem informasi pasar dalam meningkatkan pemasaran hasil produk pangan lokal sektor UMKM (Usaha Mikro, Kecil dan Menengah), serta pemanfaatan lahan pertanian yang belum termanfaatkan untuk meningkatkan kualitas dan kuantitas produk pangan lokal.